“ORPHIKON I” BY ATHANASIOS TRIKOUPIS – A “BRIDGE” BETWEEN ANCIENTAND CONTEMPORARY TIMES, A MEANS OF TEACHING MODERN MUSIC TO CHILDREN - Stela GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
One of the goals of music education is to infuse culture, to teach the ability to understand, listen to, appreciate, classify, analyse and perform music. The changes occurred in the contemporary music creation have contributed to the emergence of new complex genres that actually reach all the structural levels of compositional art, so far, as well as of arts, in general. Extremely complex in terms of form and structure, contemporary music requires a certain training and degree of knowledge in order to be adequately understood. This is why today’s music teacher is faced with a series of problems in finding various ways and methods to facilitate the children’s understanding and liking of contemporary music. The Greek composer and teacher Athanasios Trikoupis has managed to do just that, by composing Orphikon I, whose world premiere took place in Alexandroupoli, Greece, at the Scientific Session dedicated to Orpheus (1-2 October 2010). The work was performed by the Orchestra of the “Fhaëton” Conservatory in Alexandroupoli, comprised of teachers and students of that institution. By rendering modern musical garments to ancient Greek hymns, the composer has built a “bridge” between the ancient times and today. By knowing the traditions, history and culture of ancient Greece, the children found it much easier to understand the compositional concepts of modern music and they even liked it. This article presents a short analysis of this work, which highlights the approach and techniques used by the composer.